Textbook evaluation from students’ perspective: mathematics for Matriculation-Algebra / Kausar Yacob and Zahra Mardani Landani - Yacob, Kausar; Landani, Zahra Mardani (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
Textbooks as one of the instructional materials have a vital role in teaching and learning process. Textbooks may assist lecturers and students by providing guidance in a certain subject. This study aimed to evaluate the quality of the textbook entitled, “Mathematics for Matriculation: Algebra (2nd Edition)”. Garvin’s framework which was based on the eight dimensions of product quality namely, performance, features, reliability, conformance, durability, service ability, aesthetics and perceived quality was used to examine the factors affecting the perceived quality of the textbook. In addition, contextual as one new dimension was used to measure the context of this book. This study employs a quantitative method approach using self-constructed questionnaire, with 37 items. The purposive sampling was used based on the characteristics of students who used this textbook in their Mathematics learning. The total number of students who completed the survey questionnaires was 283. Both descriptive statistics and Multiple Regression Analysis (MRA) were used for analysing the data. Findings reveal that features, reliability, aesthetic and contextual aspects of the mathematics textbook have affected on the perceived quality, which can promote the processes of teaching and learning and identify how the textbook meet the students’ needs. Meanwhile, other variables such as performance, conformance and durability did not have any significant effect on the perceived quality of the Mathematics textbook. This study has provided crucial empirical information in evaluating textbooks and its factors. The findings have contributed to Garvin’s framework that expand the existing literature and related theories. Furthermore, the findings will help the lecturers to understand which dimensions of the textbook must be rectified to enhance the effectiveness of this textbook.